Localization of the cohomology of a finite galois group in a dedekind domain (1976)
LeI us take a Dedekind domain A with field of fractions K. L a finite Galois extensión of K with Galois group G and B the integral closure of A in L. then B is a G -A -module and the cohomology group  of G in B.